Answer:
g' (- 2) =
![(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/f0qcv9cek84ihznc3s7uf39dlk9xfru67q.png)
Explanation:
let y = g(x) and rearrange making x the subject, that is
y =
( multiply both sides by 1 - 4x )
y(1 - 4x) = 2 ← distribute left side
y - 4xy = 2 ( subtract y from both sides )
- 4xy = 2 - y ( multiply through by - 1 )
4xy = y - 2 ( divide both sides by 4y )
x =
![(y-2)/(4y)](https://img.qammunity.org/2022/formulas/mathematics/high-school/3y4xfg1esvfqnm3hsu7b7by71dkmni5ep2.png)
change y back into terms of x with x = g'(x)
g'(x) =
, then
g'(- 2) =
=
=
![(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/f0qcv9cek84ihznc3s7uf39dlk9xfru67q.png)